Numerical simulation of the neighborhood effects on the wind loading over standard model-scale tall buildings - Andrade, Fernando Oliveira de; Maciel, Cristiano; Filho, Roberto Carlos Moro; Marques, Marcelo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Numerical simulations of atmospheric flow were carried out in this study in order to evaluate the neighborhood effects on the wind loading over standard model-scale tall buildings. The computational models were developed by solving the steady-state Reynolds Averaged Navier-Stokes equations (RANS equations) with turbulence treated by a k-ε model. Two building positioning scenarios were simulated: scenario-1 consisted of the isolated configuration of a standard model-scale building and scenario-2 was composed of the standard building with a selected neighborhood. Both scenarios were analyzed for wind incidence angles of zero, 45, and 90 degrees. The numerical results were obtained in terms of pressure and force coefficients which allowed the determination of neighborhood factors. The simulations showed that the neighborhood influences the mean wind loading on the faces of the standard building, sometimes amplifying the load (in the case of incident winds at zero and 90 degrees), sometimes attenuating the acting forces (in the case of incident winds at zero and 45 degrees). The numerical results were compared with experimental data and showed similar orders of magnitude suggesting that the simulations correctly describe the physical behavior of the wind action.